Water crisis in Parana: Causes and consequences - Ferrari, Crislaine Trevisan da Rocha Ribeiro; Signor, Altevir (Open Science Journal, 2023)
The water crisis that Paraná is going through is unprecedented in the last 90 years. Therefore, the objective of this work is to present the problem caused by it, mainly at the Paraná State, in which it has worsened since 2019. The El Niño and La Niña phenomena have relevant role in the temporal distribution anomalies of rainfall, causing, respectively, increase or decrease in precipitation in periods of marked variation in the average temperature of the Pacific Ocean. The scarcity of rain corroborates several sectors of society. According to Department of Rural Economy (in Portuguese: Departamento de Economia Rural – DERAL), the losses computed for soybeans represent more than R 23 billion, for corn it represents a total of R 2.2 billion and for beans, the losses exceed R 395 million. All this amount will stop circulating in the Paraná economy, affecting practically all segments. The measures that must be adopted by Paraná Sanitation Company (in Portuguese: Companhia de Saneamento do Paraná – SANEPAR), together with public policies, must not be only emergency and immediate, it must be planned and implemented with a view to the long term.